EFFECTS OF ACIDIC, SALINE AND DISTILLED WATER MEDIA ON CORROSION AND MECHANICAL PROPERTIES OF NIGERIAN MILD STEEL (Journal of Metallurgy and Materials Engineering, 2024)
The effects of corrosion on the mechanical properties of mild steel in Hydrochloric acid and Sea water media havebeen investigated. Samples of mild steel coupons of sizes 36.2 mm long and 4.8 mm diameter and 45.0 mm long and 8.0 mmdiameter for tensile and impact tests respectively were immersed separately for 7,14,21,28 and 35 days in 0.5M, 1.0M, 1.5M,2.0M, 2.5M solutions of HCl, sea and distilled water. The weight loss, corrosion penetration rate, yield, ultimate tensile andimpact strength were obtained for each sample after their removal from the respective media. At the end of the 35 daysexposure time, mild steel specimen inserted in 2.5M HCl acid had lost 43.75, 38.89, 49.66 % of their yield, ultimate tensile andimpact strength respectively, the specimen inserted in sea water had lost yield, ultimate tensile and impact strength of 12.5,11.11, 15.36 % respectively while that of distilled water lost 8.75, 8.89, 13.14 % of their yield strength, ultimate tensile strengthand impact strength respectively. Results of this work would be useful for corrosion engineers in managing mild steel productsfor used in structures in the sea.